Medical simulation in pharmacology learning and retention: A comparison study with traditional teaching in undergraduate medical students - Vincenzo Arcoraci; Francesco Squadrito; Domenica Altavilla; Alessandra Bitto; Letteria Minutoli; Olivia Penna; Antonio Amato; Rosario Bruno; Vincenzo Francesco Tripodi; Angela Alibrandi; Pier Luigi Ingrassia; Paola Santalucia; et al. (Wiley, 2019)
Abstract The purpose of the study was to determine whether low‐high fidelity medical simulation improves learning and long‐lasting retention of pharmacology knowledge, compared to lecture alone, in undergraduate medical students. Ninety students, before a 45‐minute lecture, were randomized into three groups ‐ sham (S), low (LF), and high fidelity (HF) simulation ‐ to participate in an interactive simulation session. To evaluate immediate and long‐lasting retention, a 20‐item structured questionnaire on inotropic agents was administered to 90 students before and after a 45‐minute lecture, after simulation, and 3 months later. In all groups, the rate of correct answers increased after lecture, while no difference was observed between different groups (P = 0.543). After simulation, students in the HF group provided more correct answers compared to S or LF group (P > 0.001). After 3 months, a significant decrease in the number of correct answers was observed in S (P < 0.001) and LF (P < 0.001) groups, but not in the HF group (P = 0.066). Moreover, HF simulation resulted in an increased number of correct answers compared to the LF (P < 0.001) or S simulation (P < 0.001). These data suggest that advanced medical simulation teaching applied to pharmacology is associated with more effective learning and long‐lasting retention compared to lecture alone.